PENGARUH KESIAPAN BELAJAR DAN KOMUNIKASI PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI KELAS X IPS SMA NEGERI 9 KOTA JAMBI - Diliza Afrila, Rada Apriliani (Universitas Batanghari Jambi, 2019)
Abstract This study aims to determine (1) the effect of learning readiness on student learning outcomes in Economics subjects in class X IPS SMA Negeri 9 Jambi City, (2) the influence of learning communication on student learning outcomes in economic subjects in Class X IPS SMA Negeri 9 Kota Jambi, (3) the effect of learning readiness and learning communication on student learning outcomes in Economics in Class X IPS SMA Negeri 9 Jambi City. The results showed that (1) Learning Readiness influences student learning outcomes in Economics class subjects in X IPS SMA Negeri 9 Jota Jambi. This is indicated by the value of tcount> ttable namely, 2.219 > 1.984, (2) Learning Communication influences student learning outcomes in Economics subjects in class X IPS SMA Negeri 9 Jambi City. This is indicated by the value of tcount> ttable, which is 2.600 > 1.984 and (3) Learning readiness and learning communication influences the learning outcomes of students in Economics subjects in class X IPS SMA Negeri 9 Jambi City. This is indicated by the value (Fcount> Ftable, which is 3.586> 3.04) Keywords : Learning Readiness, Communication, Outcomes